b-m1 DEVELOPABLE SURFACES OF BIHARMONIC NEW TYPE b-SLANT HELICES ACCORDING TO BISHOP FRAME IN THE SOL SPACE Sol3 - Korpinar, Talat; Turhan, Essin (Işık University Press, 2012)
In this paper, we study b?m1 developable surfaces of biharmonic new type b?slant helix in the Sol3 . We characterize the b?m1 developable surfaces in terms of their Bishop curvatures. Finally, we find out their explicit parametric equations in the Sol3 .